2012
DOI: 10.1111/1754-9485.12011
|View full text |Cite
|
Sign up to set email alerts
|

Why is microcalcification missed on mammography?

Abstract: Breast screening reading for microcalcification is poorly correlated to mammographic or histological features. The majority of errors were perceptive rather than interpretative. Double reading is advocated as standard practice to reduce perceptive error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…21,22 Considering that the features of cancer lesions are varied, past research has shown that cancers that present with mixed appearances (more than one mammographic feature) are more likely to be missed and readers are more susceptible to omission error when cancers display mixed mammographic appearances. 23 Our study supports this, whereby the mammographic features of stellate lesions were associated with spiked linear extensions radiating outwards and ill-defined spicules from the central lesion which indicate the demosplastic reaction of breast cancer into surrounding tissue. 24 The distinctive features of stellate lesions have a positive-predictive value of 84-91% and are most common mammographic features of invasive breast cancer.…”
Section: Discussionsupporting
confidence: 84%
“…21,22 Considering that the features of cancer lesions are varied, past research has shown that cancers that present with mixed appearances (more than one mammographic feature) are more likely to be missed and readers are more susceptible to omission error when cancers display mixed mammographic appearances. 23 Our study supports this, whereby the mammographic features of stellate lesions were associated with spiked linear extensions radiating outwards and ill-defined spicules from the central lesion which indicate the demosplastic reaction of breast cancer into surrounding tissue. 24 The distinctive features of stellate lesions have a positive-predictive value of 84-91% and are most common mammographic features of invasive breast cancer.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, the proportion of DCIS was comparable to that in other pooled results of initial screening (17% vs 18%) (5); data obtained from 12 countries indicated that the overall DCIS detection rate in initial screening was lower from age 50 to 59 Third, data involving breast density at mammography were not available for evaluation, and this might be a confounding factor. However, about 92% of all cases of DCIS detected with digital mammography screening are associated with calcifications as a mammographic abnormality (20), which has been reported to be poorly correlated with breast density (21). Recent results seem to confirm that breast density at mammography is an important risk factor for all types of breast cancer and that it strongly increases the risk of developing an interval tumor, while this excess risk is not completely explained by a possible masking effect (22).…”
Section: Discussionmentioning
confidence: 98%
“…The digital database for screening mammography (DDSM) [35] was built by the University of South Florida, which is available for research at [36]. In our experiments, all images manually selected from this database are intensity images, digitized at 43.5  μ m/pixel and 12-bit gray scale.…”
Section: Methodsmentioning
confidence: 99%